Inventory and habitat study of Dendrobium capra J.J.Smith in Madiun and Bojonegoro - NINA DWI YULIA; NUR SHOLECHA RUSEANI (Society for Indonesian Biodiversity, 2008)
Dendrobium capra J.J. Smith or â€œanggrek larat hijauâ€ is the orchid of low land area which includes endangered orchid species, so it needs to conserve ex situ. The success of ex situ plant conservation influence environmental factor. Thatâ€™s why habitat study of D. capra needs to be done to know about how the orchid can grow well. The observation was done in Perhutaniâ€™s teak forest between Madiun and Bojonegoro, East Java which be done in three RPH is RPH Klangon (Pajaran village, Madiun), RPH Sukun (Sambongrejo village, Bojonegoro) and RPH Gondang (Bethet village, Bojonegoro). The aims of this research are for doing study habitat and knowing the number of population on wild. The result show that D. capra can found in teak and bungur trees at 5th zone because it needs to get a direct sunshine. Some environment factors are temperature of 30-33ÂºC, humidity of 40-60% and no roots moss covered. The result of inventory showed that the numbers of D. capra on areas are 45 individual in RPH Klangon, 145 individual RPH Sukun and 58 individual RPH Gondang.Â© 2008 Jurusan Biologi FMIPA UNS Surakarta.Key words: Dendrobium capra J.J.Smith, habitat, Madiun, Bojonegoro.